2005
DOI: 10.1002/jbm.a.30301
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of RGD‐coated titanium implants inserted in two bone‐gap models

Abstract: RGD (Arg-Gly-Asp) coating has been suggested to enhance implant fixation by facilitating the adhesion of osteogenic cells to implant surfaces. Orthopedic implants are unavoidably surrounded partly by gaps, and these regions represent a challenging environment for osseointegration. We examined the effects of cyclic RGD-coated implants on tissue integration and implant fixation in two cancellous bone-gap models. In canines, we inserted loaded RGD-coated implants with 0.75-mm gap (n = 8) and unloaded RGD-coated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 31 publications
5
75
3
Order By: Relevance
“…Some authors have reported that as little as 10-20% of a press-fit inserted prosthesis is in contact with the bone (Noble et al 1988, Schimmel andHuiskes 1988, Geesink 2002). Our previous work with gap implants has consistently shown abundant ongrowth of fibrous tissue, inferior bony ongrowth, and poor mechanical fixation (Soballe et al 1990, Elmengaard et al 2005. In previous studies, the titanium implant surface has been shown to be similar to that of commercially available prostheses with a plasma spray titanium coating (Soballe et al 1992(Soballe et al , 1993.…”
Section: Discussionmentioning
confidence: 97%
“…Some authors have reported that as little as 10-20% of a press-fit inserted prosthesis is in contact with the bone (Noble et al 1988, Schimmel andHuiskes 1988, Geesink 2002). Our previous work with gap implants has consistently shown abundant ongrowth of fibrous tissue, inferior bony ongrowth, and poor mechanical fixation (Soballe et al 1990, Elmengaard et al 2005. In previous studies, the titanium implant surface has been shown to be similar to that of commercially available prostheses with a plasma spray titanium coating (Soballe et al 1992(Soballe et al , 1993.…”
Section: Discussionmentioning
confidence: 97%
“…The most commonly used peptide sequence for surface modification is the above mentioned cell adhesion motif RGD (113)(114)(115). Additionally, various other peptide sequences have been immobilized onto implant materials (Table III) (99,112,(116)(117)(118)(119)(120).…”
Section: Ecm Proteins and Peptide Sequence Immobilizationmentioning
confidence: 99%
“…via functional groups like hydroxyl-, amino-, or carboxyl groups. RGD-functionalized materials are reported to improve early bone ingrowth and matrix mineralization in implanted constructs (113,121) and to induce more bone contact to the implant (114,122). Fig.…”
Section: Ecm Proteins and Peptide Sequence Immobilizationmentioning
confidence: 99%
“…With reference to cell adhesion molecules, researchers have examined the potential of Arg-Gly-Asp (RGD)-containing peptide coatings to aid both osteoblast attachment and to mimic the signalling incurred via the collagenous matrix they would ordinarily secrete. However, the in vivo evidence indicates that these material modifications offer, at best, modest improvements on the process of osseointegration (Elmengaard et al, 2005a;Elmengaard et al, 2005b;Kantlehner et al, 2000;Lutz et al, 2010;Schliephake et al, 2002). Suffice it to say, bone biomaterials modified this way are not being used as functional adjuncts for bone repair and/or regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The use of thiol-ene chemistry presented itself as a facile and relatively mild reaction route for the covalent fixation of the selected lipid species (Ganeva et al, 2003a;Ganeva et al, 2003b). Appropriate preparation of the Ti surface enables the use of silane-based functionalisation to present either a thiol reactive group for direct radical-mediated addition to the LPA double bond (Route 1a), or, as an alternative, functionalisation with an alkene-modified silane for further reaction with a dithiol (Route 1b).…”
Section: Jp Mansell Et Almentioning
confidence: 99%